Fine-tuning the efficiency of para-hydrogen-induced hyperpolarization by rational N-heterocyclic carbene design. Issue 1 (December 2018) - Rayner, Peter; Norcott, Philip; Appleby, Kate; Iali, Wissam; John, Richard; Hart, Sam; Whitwood, Adrian; Duckett, Simon
Abstract IridiumN -heterocyclic carbene (NHC) complexes catalyse thepara -hydrogen-induced hyperpolarization process, Signal Amplification by Reversible Exchange (SABRE). This process transfers the latent magnetism ofpara -hydrogen into a substrate, without changing its chemical identity, to dramatically improve its nuclear magnetic resonance (NMR) detectability. By synthesizing and examining over 30 NHC containing complexes, here we rationalize the key characteristics of efficient SABRE catalysis prior to using appropriate catalyst-substrate combinations to quantify the substrate's NMR detectability. These optimizations deliver polarizations of 63% for1 H nuclei in methyl 4, 6-d 2 -nicotinate, 25% for13 C nuclei in a13 C2 -diphenylpyridazine and 43% for the15 N nucleus of pyridine-15 N. These high detectability levels compare favourably with the 0.0005%1 H value harnessed by a routine 1.5 T clinical MRI system. As signal strength scales with the square of the number of observations, these low cost innovations offer remarkable improvements in detectability threshold that offer routes to significantly reduce measurement time. Hyperpolarization methods play a crucial role in the in vivo observation of molecular metabolism by MRI techniques. Here, the authors develop NHC-containing iridium complexes which improve the NMR detectability of1 H, 13 C and15 N nuclei via transfer of latent magnetism of para-hydrogen into a substrate.